Post-COVID-19 Hair Disorders in the City of Iguatu-PR (Research, Society and Development, 2022)
Objective: To identify the prevalence of hair disorders after COVID-19 infection in individuals from the city of Iguatu-PR. Methodology: quantitative and qualitative exploratory-descriptive research, carried out through the application of an online questionnaire to patients who attended the basic health unit of the municipality during the month of August 2022, being selected only those patients aged between 18 and 60 years that presented the infection by the new coronavirus. Results: 58.75% of respondents reported having some sequel after infection by COVID-19, in relation to hair loss, 53.75% of individuals reported the development of hair loss after infection. 55.8% of the subjects reported thinning of the hair strands, and 86% of the subjects reported that the hair loss was diffuse. As for the time elapsed until the onset of the fall, the time range varied between 1 week and 6 months or more after the infection for the first signs of fall to appear, 30.23% of people reported that the symptoms appeared 1 month after the infection. The duration of hair loss did not exceed 6 months in 81.58% of respondents, only 18.42% of the 43 patients reported that the hair loss lasted for more than 6 months. Conclusion: COVID-19 can lead to the development of hair disorders, among them, telogen effluvium is more prevalent. More information should be sought to actually clarify the relationship between COVID-19 and hair loss, studies with larger populations bring more representative results.